Guise and Disguise : Rhetoric and Characterization in the English Renaissance - Davis, Lloyd, 1959-2005 (Book collections on Project MUSE., 1993)
Davis's approach links Renaissance culture both to its past and to modern and post-modern notions of subjectivity and language.</p.